二十世纪初马来亚粤讴研究 = A study of the Yue Ou in Malaya (1904-1920) - 李成钢 Lee, Chen Kang (2013)
粤讴是一种民间文学盛行于中国广州，在19世纪，它也深受马来亚中国在20世纪初。本论文探讨岳区马来亚报纸发表在1904年至1920年的发展。 Yue Ou is a type of folk literature that prevailed in Canton, China during the 19th century and it was also popular among Malayan Chinese during early of 20th century. This thesis investigates the development of Yue Ou which published in Malayan newspaper from 1904 to 1920. The full text divides into five chapters, chapter one is an introduction stating the objectives, scope and methods of study. Chapter two discusses the history background and the dissemination of Malayan Yue Ou, summing up the reasons for its sudden emergence and quick demise. The third chapter indicates the folk literature specialities of Yue Ou such as it's orality, variability and collective nature. By comparing works by different aurthor, this chapter also outlines the writing formula of Yue Ou. Chapter four examines the orality tradition in Malayan Chinese Literature, points out the importance of Yue Ou as a representative of folk literature in current Singaporean Chinese Literature and Malaysian Chinese Literature. Chapter five, the conclusion, begins with review of the overall study, also discusses the possibilities of folk literature research in Singapore and Malaysia.